(untitled) (Research, Society and Development, 2024)
Introduction: As the population ages, the need for palliative care (PC) increases and aggressive intensive care must transition to PC. Many studies have shown numerous benefits of the palliative approach in the intensive care unit (ICU), such as decreased admissions, reduced length of stay, better symptom management, and increased satisfaction with end-of-life care. Objectives: To evaluate how many patients admitted to the ICU meet the criteria for PC and to determine how many of these patients were evaluated and what actions were taken. Materials and Methods: A retrospective, cross-sectional and observational study was carried out by collecting data from the electronic medical records of all patients who were hospitalized in the Adult ICU of the Dr. José de Carvalho Florence Municipal Hospital, between February and March 2022. Patients eligible for PC were defined as those with age greater than or equal to 80 years, need for performing tracheostomy or gastrostomy and/or presence of life-threatening underlying conditions. Results: A total of 209 new hospitalizations were analyzed, of which 43.5% were indicated for PC evaluation. Only 14.4% of the patients with indication received palliative evaluation. The main approach taken was the decision not to have cardiopulmonary resuscitation. Conclusion: The palliative approach in the ICU is extremely challenging and requires more robust studies for its consistency, however, with the results of this study we emphasize the importance of strengthening Palliative Care within the Intensive Care Unit.